PERBEDAAN PERUBAHAN KADAR KOLESTEROL TOTAL DAN TRIGLISERID ANTARA PEMAKAIAN MONOTERAPI INSULIN DENGAN TERAPI KOMBINASI INSULIN DAN METFORMIN PADA PASIEN DIABETES MELITUS TIPE II - Prita Murani Nugraheti; Erlina Marfianti; Linda Rosita (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Backround: Diabetes mellitus (DM) is a degenerative disease predicted by WHO to increase in Indonesia from 8.4 million in 2000 to around 21.3 million in 2030. Diabetes mellitus is closely related to dyslipidemia which can increase the risk of coronary artery disease (CAD). Current DM treatment is using oral hypoglycemic drugs, insulin, or a combination of both. Many previous studies have not examined the effect of these therapies on lipid profiles, specifically total cholesterol and triglyceride levels.Objective: To determine the differences in changes in total cholesterol and triglyceride levels between the use of insulin monotherapy and combination therapy of insulin and metformin in patients with type II diabetes mellitus in Sleman Yogyakarta Hospital from January 2010 toJune 2012.Methods: This study was an observational analytic study using a retrospective cohort study method with samples (n = 64). Samples were taken by non-probability consecutive sampling, carried out in DM patients inpatient or outpatient at Sleman Yogyakarta Hospital for the period of January 2010 - June 2012. The samples were divided into two groups, insulin monotherapy group and insulin and metformin combination therapy group. The data taken was the total cholesterol and the first triglyceride level, then the second total cholesterol and triglyceride data were made after four months of getting therapy.Result: Analysis of statistical data using the Mann Whitney test for changes in total cholesterol levels in the two treatment groups showed p = 0.166, whereas for changes in triglyceride levels in the two treatment groups it was found that p = 0.840.Conclusion: There were no significant differences in changes in total cholesterol and triglyceride levels between the two treatment groups.